Sustainable performance analysis and environmental protection optimization of green entrepreneurship-driven energy enterprises - Huaxing Wang; Yanzhao Zeng; Jiali Zhang; Shuhui Yu; Zeyu Wang; Yue Deng (Humanities & Social Sciences Communications)
Abstract This study investigates the impact of green entrepreneurship on the sustainable performance of energy companies, with a focus on the roles of green entrepreneurial orientation, green dynamic capabilities, and business model innovation. Through quantitative analysis of survey data, the results reveal a significant positive correlation between green entrepreneurial orientation and sustainable performance. Furthermore, green dynamic capabilities and business model innovation act as mediating factors in this relationship. The findings suggest that strategies aimed at optimizing environmental protection can also enhance sustainability. This study highlights the importance of integrating green innovation and optimizing conservation strategies, offering valuable insights and recommendations for improving the sustainable development capabilities of companies in the energy industry.